Farmer’s Share, Margin dan Efisiensi Pemasaran Telur Ayam Ras - Stevy P Pangemanan; Inggriet D R Lumenta; Theresa Maliangkay (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2023)
The purpose of this study was to determine the farmers' share and marketing efficiency of purebred chicken eggs. This research was conducted in January 2023. The research method used is the survey method. The sampling technique was purposive sampling with the Snow Ball Sampling technique. Data analysis includes marketing costs, marketing margins, farmer's share, profit and cost ratios and marketing efficiency of each marketing channel. The results of this study show that the largest farmer's share is 81.66%, the ratio of benefits and costs is the largest, namely 11.47. The smallest farmer's share is 69.04%, the smallest profit and cost ratio is 5.86, and the biggest marketing cost is IDR 4,705. Level I and level II channels of marketing of purebred chicken eggs in Talawaan District are efficient with a value 1.